Operations management curriculum development under uncertain situations: lessons learned from the pandemic - Stavropoulou, Foteini; Panjehfouladgaran, Hamidreza; Teimouri, Misha (Institute for Operations Research and the Management Sciences, 2024)
The COVID-19 pandemic caused a major disruption to higher education as faceto- face teaching had to shift to distance teaching overnight. In this paper, we describe the adaptation of an operations management undergraduate core module, taught to first-year students, from face-to-face delivery to emergency online delivery. In our online version, we used a mix of traditional and flipped classroom techniques. We adopted a "live"online lecture, where students were encouraged to interact with their instructors and ask questions, and flipped live online tutorials, where students and instructors discussed case studies. In addition, we used a web-based simulation game as a learning and assessment tool. After the simulation game was complete, we assessed our students using a reflective group presentation regarding the decisions they made throughout the game. Based on student feedback, the curriculum design and the module adaptations that we adopted for its emergency online delivery can be considered successful. In particular, students were satisfied with the module quality and structure. Following our experience from adapting our face-to-face module for emergency online delivery, we provide a framework for switching to emergency online teaching along with some useful insights and recommendations to operations management educators.